(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Forensic pathologists come across natural deaths only when it is sudden. Sudden natural deaths are mostly due to the involvement of the cardiovascular system and followed by the involvement of central nervous system. Here, we report a case of young air force personnel without any prior medical history, who collapsed at the morning exercise session and was declared brought dead. At autopsy, the cause of death was attributed to a spontaneous intracerebellar haemorrhage. Spontaneous cerebellar haemorrhage is defined as bleeding into cerebellar parenchyma without any trauma and constitutes a very small percentage of all intracerebral haemorrhages. Cerebellar haemorrhage is most commonly caused by hypertension and other causes are aneurysms, vascular malformations, coagulopathies and tumour bleeding. Thus, this case report is being presented to stress on the need for an extensive medical examination for recruits in armed forces instead of the routine screening tests.